2020
DOI: 10.5547/01956574.41.2.lwen
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Effects of Wind Generation and Its Implication for Wind Farm Investment Decisions in New Zealand

Abstract: Spill-over effects on electricity nodal prices associated with increased wind generation have not been examined in the literature. To examine these effects, we use spatial econometric models to estimate the direct and indirect effects of wind generation on nodal wholesale electricity prices. Spatial econometric models allow us to provide quantitative estimates of spill-over magnitudes and statistical tests for significance. Results show negative and significant effects are associated with increases in wind pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…The merit order effect was calculated, for example, for Denmark, Germany, and Spain; 10 the Czech Republic; 11 and New Zealand. 12 Regardless of the approach taken and the renewable energy analyzed, however, the authors found a negative effect of higher renewable energy penetration on the wholesale market price of electricity. An exception is the solar PV technology in the Czech Republic, which is found to have a positive effect on wholesale electricity prices.…”
Section: Literature Reviewmentioning
confidence: 98%
See 1 more Smart Citation
“…The merit order effect was calculated, for example, for Denmark, Germany, and Spain; 10 the Czech Republic; 11 and New Zealand. 12 Regardless of the approach taken and the renewable energy analyzed, however, the authors found a negative effect of higher renewable energy penetration on the wholesale market price of electricity. An exception is the solar PV technology in the Czech Republic, which is found to have a positive effect on wholesale electricity prices.…”
Section: Literature Reviewmentioning
confidence: 98%
“…On the other hand, expansion of solar electricity generation in a market based on merit order (economic) dispatch can reduce the price of electricity in the wholesale market because the marginal cost of solar electricity generation is zero (merit order effect, examined for various European countries by, e.g., Welisch et al., 10 Luňáčková et al., 11 and Wen et al. 12 ). This reduction in wholesale electricity prices in the absence or reduction of economic support for solar projects can eventually transfer to electricity retail prices, helping to achieve the promise of clean and affordable electricity.…”
Section: Introductionmentioning
confidence: 99%
“…There are human factors in the setting of SWM, so that the results will be affected by different weight matrix settings [79]. To avoid the bias caused by SWM, we use the K-neighbor SWM and distance-neighbor SWM to conduct the robustness check.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…We also expect the electricity price to fall since the electricity generated by low marginal cost technology can meet the low electricity demand based on the merit-order effect. That is, the cheapest form is dispatched first, and the most expensive conventional generation is dispatched last [11] . New Zealand responded to COVID-19 with a strong “go hard, go early” approach.…”
Section: Introductionmentioning
confidence: 99%